Análise da comercialização da carne bovina no Estado de São Paulo - Carmo, Izairton Martins do (1969)
This study focuses on certain problems related to the supplying of beef to the city of São Paulo. An attempt is made to describe the present system of distribution of beef, determine profit margins in operation and the policies of both wholesale and retail suppliers, in this way identifying the principal problems related to beef marketing. Basic, secondary data were used gathered from the Institute of Agricultural Economics of the Secretary of agriculture of the State of São Paulo and the Brazilian Institute of Geography and Statistes. Managers of cold storage plants and of transportation companies were interviewed and asked, to fill ou schedules. This was done both for distributors of frozen meats and for live animals.